“The art of dividing” : la forme du chapitre dans Tom Jones de Henry Fielding - Christophe LESUEUR (E-REA)
This article undertakes to examine the form of the demarcative system in Fielding’s fiction. The peculiar prefatory devices in Tom Jones are first analyzed before the study moves on to the question of the intitulation of its chapters. This article investigates the form both chapter and book harbor in Tom Jones as well as their relationship to time so as to advance what must be called a poetics of the chapter and of the novelistic disposition.